Coronary Stents Crack and Corrode in vivo: A Structural Integrity and Tissue Inflammation Analysis - Kapnisis, Konstantinos (Department of Mechanical Engineering and Materials Science and Engineering, Faculty of Engineering and Technology, Cyprus University of Technology, 2015)
Even though stents are routinely used in the majority of cardiovascular catheterization procedures to treat stenotic arteries, their clinical effectiveness is hindered by numerous post deployment complications such as biocorrosion and structural failure, which may lead to inflammation, thrombosis and ultimately in-stent restenosis (ISR). Recent studies on explanted stents obtained from human cadavers have revealed that stents undergo corrosion and fatigue-induced fracture in vivo, with significant release of metallic ions into surrounding tissues. Corrosion by-products such as metallic ions and particulates could alter the local tissue environment leading to upregulation of proinflammatory factors and potentially promoting ISR. To investigate the role of biomechanical loading and its contribution to increased fatigue wear of stents, accelerated pulsatile durability tests were carried out on commercially available stents in a simulated physiological environment. Potential spatial variations in the mechanical properties on stent struts and their role in the observed premature failures of the stent devices during operation were also examined. Fretting wear and fatigue-induced fractures were found on stent surfaces after exposure to cyclic loading similar to that arising in vivo. Biomechanical factors such as arterial curvature combined with stent overlapping enhance the incidence and degree of wear and fatigue fracture. Nanoindentation studies performed on various locations along the stent struts have shown that the hardness of specific stent locations significantly increases after mechanical expansion. The increase in hardness was associated with a reduction of the material‘s ability to dissipate energy in plastic deformations, therefore an increased vulnerability to fracture and fatigue. It was concluded that the locations of fatigue fractures in stent struts are controlled not only by the geometrically-driven stress concentrations developing during cyclic loading but also by the local material mechanical changes that are imparted on various parts of the stent during the deployment process. Additionally, the project focused on investigating potential mechanisms and regulatory factors involved in the development of in-stent restenosis. The effect of stent corrosion was investigated in an animal model in order to explore a possible link between metal ion release, inflammation, and factors thought to initiate ISR. To evaluate the vessel inflammatory response, miniature stents with active corrosion were implanted in mice abdominal aortas and novel in vivo imaging techniques were employed to assess the trafficking and accumulation of fluorescent donor monocytes as well as the proliferation of vascular smooth muscle cells at the implantation site. The in vivo imaging analysis revealed that elevated metal particle contamination, prompted by corroded stents, triggers an inflammatory response and promotes monocyte recruitment and neointimal proliferation at the site of injury. The results suggest that when stents corrode in vivo, the generated active microenvironment promotes inflammation that may lead to the development of in-stent restenosis. The project findings are consistent with what has been recently reported regarding the condition of explanted stents from human cadavers, proposing the need for optimization of future stent designs and modification of current regulatory testing guidelines. Future work will focus on developing novel strategies to address the serious complications arising from the ubiquitous use of cardiovascular stent implants. This will eventually lead to the design of new biofunctional stent platforms that will help the millions of cardiac patients worldwide who suffer from ISR complications.
Keywords: Cardiovascular catheterization procedures; Inflammation; Thrombosis; In-stent restenosis (ISR).